1992
DOI: 10.21236/ada254342
|View full text |Cite
|
Sign up to set email alerts
|

On-Orbit Supervisor for Controlling Spacecraft

Abstract: Public reoorting Durden for this collection of information is estimated to average I hour oer resoonse. including the time for reviewing instructionfs.searcling existing data sources.gathering and maintaining thedata needed, and completing and reviewing the collection of information. Send comments rejarding this burden estimate or any other aspect of tris collection of information. ncluding suggestions for reducing this ourcden to Washington Headouarters Services, Directorate for information Operations and Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In his important paper on stellar nucleosynthesis Cameron (1955) suggested that the excess of Li in WZ Cas and WX Cyg was due to the reaction 3 He( 4 He ; ) 7 Be followed by 7 Be(e ? ; ) 7 Li in a convective region that brought the 7 Be or 7 Li to cooler regions before the 7 Li was destroyed by 7 Li(p ; ) 4 He. Of course, convective regions have down-drafts as well as up-drafts.…”
Section: Lithium In Carbon Starsmentioning
confidence: 99%
“…In his important paper on stellar nucleosynthesis Cameron (1955) suggested that the excess of Li in WZ Cas and WX Cyg was due to the reaction 3 He( 4 He ; ) 7 Be followed by 7 Be(e ? ; ) 7 Li in a convective region that brought the 7 Be or 7 Li to cooler regions before the 7 Li was destroyed by 7 Li(p ; ) 4 He. Of course, convective regions have down-drafts as well as up-drafts.…”
Section: Lithium In Carbon Starsmentioning
confidence: 99%